2012
DOI: 10.1007/s00467-012-2364-9
|View full text |Cite
|
Sign up to set email alerts
|

Hypophosphatemia and growth

Abstract: Over the last decade the discovery of fibroblast growth factor 23 (FGF23) and the progressive and ongoing clarification of its role in phosphate and mineral metabolism have led to expansion of the diagnostic spectrum of primary hypophosphatemic syndromes. This article focuses on the impairment of growth in these syndromes. Growth retardation is a common, but not constant, feature and it presents with large variability. As a result of the very low prevalence of other forms of primary hypophosphatemic syndromes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 70 publications
1
49
0
1
Order By: Relevance
“…X-linked hypophosphatemic rickets is the seminal example of excess FGF23 action. It can be diagnosed during the first year when suspected by family history and early onset of hypophosphatemia (452), but in the absence of family history it more often presents at 2 or 3 years of age with bowing of the long bones or growth failure, or at later ages with short stature (102,172,588). In four cases in which affected parents prompted an early diagnosis, serum phosphorus was low in all four between 2 and 6 wk of age, tubular reabsorption of phosphorus was low at 9 days of age in one but normal in the others until 6 mo, and radiographic findings of rickets did not develop until 3-6 mo (452).…”
Section: E Human Datamentioning
confidence: 99%
“…X-linked hypophosphatemic rickets is the seminal example of excess FGF23 action. It can be diagnosed during the first year when suspected by family history and early onset of hypophosphatemia (452), but in the absence of family history it more often presents at 2 or 3 years of age with bowing of the long bones or growth failure, or at later ages with short stature (102,172,588). In four cases in which affected parents prompted an early diagnosis, serum phosphorus was low in all four between 2 and 6 wk of age, tubular reabsorption of phosphorus was low at 9 days of age in one but normal in the others until 6 mo, and radiographic findings of rickets did not develop until 3-6 mo (452).…”
Section: E Human Datamentioning
confidence: 99%
“…Familial HR consists of a group of renal phosphate wasting disorders with hypophosphatemia and inappropriately low or normal serum 1,25-dihydroxyvitamin D (1,25(OH) 2 D) levels (Morey et al, 2011). Familial HR is characterized by marked clinical variability of growth retardation, childhood rickets, osteomalacia, and poor dental development (Dixon et al, 1998;Goji et al, 2006;Morey et al, 2011;Santos et al, 2013). In addition, extraskeletal bone formation, osteoarthritis, limitation of joint mobility, and occasionally spinal cord compression may occur (Dixon et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that average incidence of HR is 3.9 per 100,000 in children between age 0 and 0.9 years, and a prevalence of 4.8 per 100,000 in those younger than 15 years (Beck-Nielsen et al, 2009). Six types of hereditary HR have been identified, including the common X-linked dominant HR (XLHR, MIM 307800), the occasional autosomal dominant HR (ADHR, MIM 193100), autosomal recessive HR (ARHR1, MIM 241520, and ARHR2, MIM 613312), the rare X-linked recessive HR (MIM 300554), and two peculiar rare forms of HR associated with hypercalciuria (HHRH, MIM 241530) and hyperparathyroidism (MIM 612089) (Morey et al, 2011;Baroncelli et al, 2012;Santos et al, 2013). HR may be caused by mutations of genes involved in the complex regulation of phosphate metabolism (Baroncelli et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The system of SSC-based gene therapy, in addition to the potential use in cases in which the father carries a homozygous genetic defect, could also be applied to treat the following genetic conditions: (1) male infertility induced by genetic defects, (2) father-carrying dominant disease alleles, and (3) sex chromosome-linked dominant genetic diseases [46][47][48].…”
Section: Discussionmentioning
confidence: 99%